Pengaruh Kompetensi Kepribadian dan Kompetensi Sosial Guru Pendidikan Agama Islam Terhadap Akhlak Peserta Didik Kelas VIII SMP Negeri 1 Sidomulyo Kecamatan Sidomulyo Kabupaten Lampung Selatan - Windari, Ayu; Syafe'i, Imam; Amriyah, Chairul (CV. Creative Tugu Pena, 2024)
Through research on the effect of Personality Competency and Social Competence of Islamic Religious Education Teachers on the Morals of Class VIII Students at SMP Negeri 1 Sidomulyo, South Lampung Regency. The aim of the research is (1) To explain the Effect of Teachers' Personal Competencies on the Morals of Class VIII Students at SMP Negeri 1 Sidomulyo . (2) To explain the Effect of Teacher Social Competence on the Morals of Class VIII Students at SMP Negeri 1 Sidomulyo. (3) To explain the Effect of the personality and social competence of Islamic religious education teachers on the morals of Class VIII students at SMP Negeri 1 Sidomulyo, South Lampung Regency. The type of research in this research is a type of causal relationship associative research with a descriptive quantitative approach. The population in this study were all class VIII students at SMP Negeri 1 Sidomulyo in the 2023-2024 academic year, totaling 258 students, the sample was 28 students and the sampling technique used simple random sampling or randomly. Data collection techniques in this research used questionnaires, interviews and documentation. The data obtained were analyzed using data analysis techniques in the form of normality, linearity, multiple regression and determinant coefficient analysis. The conclusions of this research are (1) There is an Effect of the Personality Competence of Islamic Religious Education Teachers on the Morals of Class VIII Students at SMP Negeri 1 Sidomulyo. (2) There is an Effect of the Social Competence of Islamic Religious Education Teachers on the Morals of Students in the Class VIII Islamic Religious Education subject at SMP Negeri 1 Sidomulyo. (3) There is an Effect of the Personality Competence and Social Competence of Islamic Religion Education Teachers on the Morals of Class VIII Students at SMP Negeri 1 Sidomulyo.